POLYCHRONOUS ORIGIN OF THE ANGARA-VITIM BATHOLITH - Nenakhov V.M.; Nikitin A.V.; Doronina N.A.; Matukov D.I.; Lepekhina E.N.; Berezhnaya N.G. (My University, 2007)
In recent works devoted to the age and origin of magmatic complexes of the Transbaikal region, one can see a tendency to revise the timing of maximal tectonomagmatic activity in this region. The generally accepted concepts on the Late Precambrian age of the major orogenic pulse of magmatism are questioned, while ancient magmatic complexes are “rejuvenated.” It is now evident that there was no global tectonic event in the western Transbaikal region. Instead, the region was involved in permanent epicratonic orogenesis that was manifested during the entire post-Riphean stage, the Phanerozoic included.
Keywords: Paleozoic::Silurian; Палеозой::Силурийская